2017
DOI: 10.1590/1983-21252017v30n308rc
|View full text |Cite
|
Sign up to set email alerts
|

Botanical Identification and Genetic Diversity in Melons From Family Farming in the State of Maranhão

Abstract: -The aim of this work was to perform botanical identification and to estimate genetic diversity in two sequential inbred generations (progenies S 1 and S 2 ) of melon accessions from traditional agriculture in the state of Maranhão, in order to generate useful information for commercial melon breeding. Two field experiments were carried out in a completely randomized block, using four replicates of 15 accessions from a first selfing cycle in 2013, and three replicates of 25 subaccessions (generation S 2 ) in 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 23 publications
2
8
0
Order By: Relevance
“…The data of analysis of variance showed significant differences among melon sub-accessions for all characteristics evaluated (Table 2), denoting the existence of genetic variability among sub-accessions. Similar results were found in previous studies on melon accessions from traditional agriculture (AMORIM et al, 2016;MACÊDO et al, 2017;ANDRADE et al, 2019), supporting those found in the present study and, therefore, denoting the possibility of selecting agronomically superior accessions for the characteristics analyzed (CRUZ; REGAZI; CARNEIRO, 2012). Means followed by same lowercase letter in the columns, or uppercase letter in the rows, are not statistically different from each other by the Scott Knott test at 5% significance.…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…The data of analysis of variance showed significant differences among melon sub-accessions for all characteristics evaluated (Table 2), denoting the existence of genetic variability among sub-accessions. Similar results were found in previous studies on melon accessions from traditional agriculture (AMORIM et al, 2016;MACÊDO et al, 2017;ANDRADE et al, 2019), supporting those found in the present study and, therefore, denoting the possibility of selecting agronomically superior accessions for the characteristics analyzed (CRUZ; REGAZI; CARNEIRO, 2012). Means followed by same lowercase letter in the columns, or uppercase letter in the rows, are not statistically different from each other by the Scott Knott test at 5% significance.…”
Section: Resultssupporting
confidence: 93%
“…Prolificacy and fruit cavity diameter presented only 18.5% variation, highlighting the variety makuwa and botanical varieties not defined (ND), respectively. Regarding the other characteristics, the highest variations were found for sub-accessions of ND varieties (Table 2); these variations are probably because of the high variability among plants within the sub-accessions, which is due to the introgression of alleles among different botanical varieties (MACÊDO et al, 2017;AMORIM et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations